2019
DOI: 10.1007/s11092-019-09295-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of linguistic similarity on cross-cultural comparability of students’ perceptions of teaching quality

Abstract: Valid cross-country comparisons of student learning and pivotal factors contributing to it, such as teaching quality, offer the possibility to learn from outstandingly effective educational systems across the world and to improve learning in classrooms by providing policy relevant information. Yet, it often remains unclear whether the instruments used in international large-scale assessments work similarly across different cultural and linguistic groups, and thus can be used for comparing them. Using PISA 2012… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In addition, scientific studies measuring observed teaching quality involving multiple countries are currently not present, especially in the context of secondary education (cf. André et al, 2020;Fischer et al, 2019). This study is among the first to address this gap.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, scientific studies measuring observed teaching quality involving multiple countries are currently not present, especially in the context of secondary education (cf. André et al, 2020;Fischer et al, 2019). This study is among the first to address this gap.…”
Section: Introductionmentioning
confidence: 94%
“…A recent systematic review research effort reported by Aidoo and Shengquan (2021) draws a distinction between the terms "teaching" and "teaching quality." Nevertheless, in order to identify teaching, some of the authors referenced by Aiddo and Shengauan observe actions related to both teacher's behavior during class (teaching), and instruction capacity circumstances (teaching quality) (Klieme et al, 2009;Bell et al, 2012;Hafen et al, 2014;Grosse et al, 2017;Fischer et al, 2019). When referring to teaching quality, characteristics such as emotional support, instructional support, classroom organization, type of cognitive demand, and class organization and management are described, among others (Gitomer et al, 2014;Joyce et al, 2018;Liu and Cohen, 2021).…”
Section: Teaching and Feedback In The Students' Learningmentioning
confidence: 99%
“…As the IA approach is implemented in the popular Mplus software since its inclusion in Version 7.1 (May 2013; see [76]), it was already employed in a broad range of applications [40,75,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. The applications are most frequently found in the disciplines of education science, political science, psychology, and sociology.…”
Section: Previous Simulation Studies and Applicationsmentioning
confidence: 99%